Peran Dakwah Islam Dalam Menciptakan Nilai-Nilai Moderasi Beragama Pada Remaja di Kelurahan Bukit Sangkal Palembang - Harris Febriyan; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2024)
This research is entitled: "The Role of Islamic Da'wah in Creating Religious Moderation Values in Adolescents in Bukit Sangkal Subdistrict, Palembang". The issues discussed in this thesis are: What is the role of Islamic preaching in creating values of religious moderation in teenagers in Bukit Sangkal Village, Palembang and what are the supporting and inhibiting factors in creating religious moderation values in teenagers in Bukit Sangkal Village, Palembang. The aim of this research is: To determine and analyze the role of Islamic da'wah in creating values of religious moderation among teenagers in Bukit Sangkal Village, Palembang. This research uses qualitative research. The data collection technique in this research uses interview, observation and documentation methods. The data analysis technique used in this research is the technique from Miles and Huberman, namely data reduction, data presentation and drawing conclusions. The results of the research show that while there is still a generation that does not accept an attitude of religious moderation, we must be able to provide a deep understanding of what religious moderation is, and explain that we do not live alone, we live together with other identities, which are based on the concept of our beliefs. different, our understanding is different, but in matters of togetherness it contains good values which actually do not conflict with what we believe in, we must unite to succeed in building harmony in differences. So the thing that needs to be avoided is coercive behavior in inviting someone to believe in what we believe in. In a life of diversity we must be able to make religious moderation into our character, so that it is easy to apply to everyday life.